"Helping Caritas build lives again" an evaluative study on the public service advertisements of Caritas Manila on television and the effectiveness of advertisements in influencing Cainta residents to support the institution's programs for the street children - Del Rosario, Caroline C.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This evaluative study on the communication strategies of Caritas Manila on their public service ads on television and their effectiveness in influencing Cainta residents to participate in the programs of the institution, used the survey method, content analysis, and focused interviews to obtain necessary data. Residents from Metroville 2 and Cainta Greenpark Phase 9 were selected as respondents through the simple random sampling technique. The content analysis method was employed to analyze the communication strategies and approaches used in the four public service advertisements of Caritas Manila. Focused Interviews were conducted to acquire first-hand data, particularly from volunteers Liza Gaa, Bernadette Cariño, and Elenita Virmud. Data from the survey revealed that the respondents have a high level of television exposure. It was likewise concluded that Caritas Manila is known among the respondents from Cainta. This indicates that they have a high level of knowledge of Caritas mainly due to the respondents' high level of exposure to the public service advertisements. This attributed to the tremendous effect of mass media, particularly the television to familiarize its audiences about almost everything under the sun. It is also interesting to note that despite the rare airing of the ads on television, certain dialogues and pictures from the ads were retained in the minds of the respondents. Majority of the respondents gave a general description of the ads as appealing to one's emotions. However, although these ads appeared to be emotionally appealing for the respondents, only a few described the ads as influencing enough to urge them to help Caritas in their missions and programs. Some described the ads as educational. The rest did not give any comment at all. Since only a small portion of the respondents described the ads as influencing, no one among the respondents has participated in any of the programs of Cartitas after their exposure to the ads. Hectic schedule and unawareness of the programs were the major reasons for not having participated in any of the programs. It was found that the respondents' level of knowledge of Caritas was largely affected by their exposure to mass media, particularly television and print materials. Based on the results, the public service advertisements of Caritas Manila on television are neither effective nor ineffective. Conclusion was based on the measures that in order to declare the effectiveness of the ads among the respondents, they must have complied to the following conditions indicated in this study: expressed willingness to help Caritas Manila in their programs and voluntary participation after exposure to the ads. Basic Advertising may have applied good communication strategies in their ads but the respondents may have found them to be just like any public service ad they see on television.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Caritas, Charity -- Philippines -- Advertisements